Dynamics of bio-convection agrawal axisymmetric flow of water-based Cu-TiO2 hybrid nanoparticles through a porous moving disk with zero mass flux - B.C. Prasannakumara; Khan, Umair; Ishak, Anuar; Zaib, Aurang; Waini, Iskandar; Raizah, Zehba; Galal, Ahmed M. (Elsevier B.V., 2022)
Modern electronic equipment frequently encounters thermal critical difficulties as a result of increased heat production or a reduction in effective surface area for heat exclusion. This most intriguing problem can be solved by either improving an optimal structure for the cooling system or improving heat transfer performance. In this case, nanofluid performs well in addressing all of these issues. In addition, the structure of boilers necessitates a thorough understanding of the two-phase flow behavior of heat transfer and pressure drop, which varies substantially from that of single-phase flow. The present works address the features of Agrawal axisymmetric flow induced by hybrid nanofluid with motile microorganisms past a porous moving disk with zero mass flux. Through the use of similarity variables, the partial differential equations that represent the two-phase flow problems are eased to ordinary differential equations and then used a bvp4c technique to find the numerical dual solutions. The influences of pertaining control parameters on the dimensionless friction factor, the heat transfer, and the motile microorganisms are investigated and portrayed in both the form of graphical illustrations as well as in the form of tables. The obtained results show that an upsurge in the solid volume fraction of nanoparticles leads to substantial magnification of the shear stress and heat transfer for both branches while the local motile microorganism flux reduces. In addition, the friction factor, motile microorganism flux, and heat transfer are enhanced due to the presence of suction.